Contact Sensitization in Children: A Retrospective Study of 2, 614 Children from a Single Center. Issue 4 (31st May 2016) - Belloni Fortina, Anna; Fontana, Elena; Peserico, Andrea
Abstract: Background: Contact sensitization in children is more common than previously thought, but few studies have been performed on a large population assessed by the same team. The objective was to evaluate contact sensitization in children with suspected contact dermatitis, the relationship with atopic dermatitis (AD), and the most common allergens. Methods: The same team patch tested 2, 614 children younger than 11 years old with a standard series of 30 allergens. Results: A total of 1220 children (46.7%) developed at least one positive reaction, 606 of which were clinically relevant (49.7%). The most frequent reactions were to nickel sulfate (22.7%), cobalt chloride (11.1%), potassium dichromate (9.9%), neomycin sulfate (5.2%), thimerosal (4.2%), cocamidopropyl betaine (3.4%), and methylchloroisothiazolinone/methylisothiazolinone (3.2%). The prevalence of contact sensitization was similar in children with (47.3%) and without (46.1%) AD. Children with AD had a higher prevalence of positive reactions to potassium dichromate (p < 0.001), Compositae mix (p = 0.01), and disperse blue (p = 0.03). Conclusions: Contact sensitization is quite common in young children. This study adds some information on the most common contact allergens. A similar prevalence of positive patch test reactions was found in children with and without AD, but children with AD had a greater prevalence of positive patch test reactions to potassium dichromate, Compositae mix, and disperse blue.